Avaliação crítica de um sistema de reúso de águas cinzas - Baicere, Gonçalo Santana (2014)
The growth in the consumption of potable water has reflected directly in the increase of pollution and quantitative and qualitative degradation of the water bodies, receptors of releases of untreated wastewater. Thus, the development of measures and programs that will enable conservation and reduction of potable water consumption is becoming a priority for some institutions. This study aims to develop and evaluate a simplified treatment and operation technology to take advantage of laundry water as an alternative source of supply for toilet flushing in homes. Thus it was necessary to characterize the physical, chemical and microbiological aspects of the gray water coming from the washing machines. The experimental treatment system was operated and monitored for a period of 12 months, in a house with five people. The Experimental Station was composed of a decanter, followed by an aerobic sand filter and disinfection with a filter with sodium hypochlorite at 2% (bleach). Besides evaluating the efficiency of the experimental station in accordance with the physical, chemical and microbiological standards of the existing guidelines and recommendations, the consumption of potable water of the households were monitored, in order to verify if there was a reduction in the consumption measured by the sanitation utilities, after the implementation of the treatment system. The treatment system adopted showed a high efficiency in the average removal of turbidity, color, nitrate, total coliforms and Escherichia coli, of 93.52, 94.18, 86.27, 100 and 100%, respectively. In relation to BOD5, (Biochemical Oxygen Demand) COD (Chemical Oxygen Demand) and TSS (Total Suspended Solids), the system presented an average removal efficiency of 58.04, 55.72 and 60.29%. The effluent of the treatment system has characteristics which are compatible with several parameters established for the non potable reuse.